Tabarruk dalam Pandangan Ulama’ Sunni dan Syi’ah dan Implementasinya dalam membangun karakter umat Islam: Studi Komparasi Pemikiran Zaynu Al-Abidin Ba’alawi dan Ja’far Subhani - Layyinah Nur Chodijah; Farida Ulvi Naimah (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The debate over the implementation of Tabarruk is something that still raises a lot of debate among the Muslims of the world. The majority of Muslims are very enthusiastic about carrying out this practice, while others still consider tabarruk an act of heresy and even shirk. In this literature study, the author will try to re-present the concept and understanding of tabarruk from the perspective of Sunni and Shia scholars as active adherents of tabarruk practice which will be represented through the thoughts of the two figures in this group, namely Zainal Abidin al-Ba'lawi and Ja 'far Subhani. From this concept, the author will relate the implementation to the impact of tabarruk practices in building the character of Muslims. The research used in this study is a comparative approach with a qualitative description in which the thoughts of these two figures will be coordinated and compared so as to produce a neutral and impartial. The results of this study state, that the Ahlussunnah and the Shiah have mutually agreed, that the practice of tabarruk is a legal practice and can be carried out by all Muslims in the agreed measure and rules. Therefore, these results are used as a response to criticism from parties who oppose the practice of tabarruk with accusations of polytheism and are considered to be detrimental both financially and morally for Muslims. In addition, the practice of tabarruk carried out in accordance with the Shari'ah has a positive impact on the character building of Muslims. Among the kinds of tabarruk in religious practice are: reading the Qur'an, visiting graves, seeking knowledge, and tabarruk with Sayyidina Husein's turban.